2004
DOI: 10.1359/jbmr.0301224
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Screen of a Large Twin Cohort Reveals Linkage for Quantitative Ultrasound of the Calcaneus to 2q33–37 and 4q12–21

Abstract: A genome-wide screen was performed on a large cohort of dizygous twin pairs to identify regions of the genome that contain QTL for QUS of bone. Suggestive linkage of QUS parameters to 2q33-37 and 4q12-21 highlighted these regions as potentially important for studies of genes that regulate bone. Introduction:The genetics of osteoporotic fracture is only partly explained by bone mineral density (BMD). Quantitative ultrasound (QUS) of the calcaneus can also be used for independent clinical assessment of osteoporo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Subjects were assessed for an extensive range of phenotypes. Genome-wide linkage scans for bone 21,22 and eye disease 23 have been reported previously for this cohort. Here we report the data from genome-wide linkage scans for obesity-related traits (n ¼ 2188 individuals).…”
Section: Subjects and Clinical Assessmentmentioning
confidence: 78%
“…Subjects were assessed for an extensive range of phenotypes. Genome-wide linkage scans for bone 21,22 and eye disease 23 have been reported previously for this cohort. Here we report the data from genome-wide linkage scans for obesity-related traits (n ¼ 2188 individuals).…”
Section: Subjects and Clinical Assessmentmentioning
confidence: 78%
“…Linkage studies have been spectacularly successful in identifying the genes that are responsible for rare, monogenic bone diseases characterized by abnormalities of bone mass such as osteopetrosis and sclerosing bone dysplasias (Janssens and Van Hul 2002;Balemans et al 2005). Linkage analysis has also been applied to the identification of chromosomal regions that harbor genes that regulate quantitative traits such as bone mass, bone geometry, and ultrasound properties of bone in the normal population (Koller et al 2003;Wilson et al 2003Wilson et al , 2004Ralston 2005). Linkage studies in osteoporosis classically involved genotyping a series of polymorphic microsatellite markers, typically spread at 10-cM intervals throughout the genome, and relating inheritance of alleles to the inheritance of bone mass within the family members.…”
Section: Linkage Analysis In Humansmentioning
confidence: 99%
“…For example, genome-wide linkage scans have identified several QTL that strongly influence hip geometry (Koller et al 2001), while others have been performed that have identified QTL that regulate the quantitative ultrasound properties of bone (Wilson et al 2004).…”
Section: Human Linkage Studiesmentioning
confidence: 99%